Advances in engineering design select proceedings of ICOIED 2020 - Cheng, Franklin Y.; Sheu, Maw Shyong; Rakesh, Pawan Kumar; Sharma, Apurbba Kumar; Singh, Inderdeep
This book presents the selected peer-reviewed proceedings of the International Conference on Innovative Engineering Design (ICOIED 2020). The contents provide a multidisciplinary approach for the development of innovative product design and their benefits for the society. The book presents latest advances in various fields like design process, service development, micro/nano technology, sensors and MEMS, and sustainability in engineering design. This book can be useful for students, researchers, and professionals interested in innovative product/process design and development.